Paying more to hire the best? Foreign firms, wages and worker mobility - Pedro Silva Martins (Institute for the Study of Labor (IZA), 2008)
In the context of the debate on the labour-market consequences of globalisation, we examine worker mobility in order to identify the wage differences between foreign and domestic firms. Using matched employer-employee panel data for Portugal, we consider virtually all spells of interfirm mobility over a period of ten years. We find that foreign firms offer significantly more generous wage policies, although there is also a (smaller) selection effect. The results are robust to the consideration of wage growth differences, the case of displaced workers and different subsets of workers.
urn:nbn:de:101:1-2008072929
Keywords: J31; 330; Foreign direct investment; worker displacement; wage growth; Arbeitsmobilität; Lohnstruktur; Multinationales Unternehmen; Unternehmen; Portugal